COMMON SECURITY DENOMINATOR OF THE WESTERN NALKANS IN THE THIRD DECADE OD 21ST CENTURY: RISKS, OBSTACLES AND OPPORTUNITIES (Security Dialogues, 2025)
The purpose of this paper is to identify the key security risks in the area of theWestern Balkans, which are actually the common denominator in attempts at cooperation,coordination and integration in the field of creating defense and security policies, on regionaland national level. Apart from the identification of security risks that determine the viabilityof Western Balkan actors, the fact that it is a region that is not fully integrated within theNATO defense and security infrastructure, partial integration will be used as a variable in theanalysis of cooperation opportunities, in the political and contractual context. Finally, thecapacities of regional cooperation in the field of security, determined by bilateral and regionalagreement frameworks, will be presented. The contribution of this work in a scientific sensewill be the answer to the question of how much the potential joint action of small states inthe face of modern security risks affects the process of creating security sustainability at theindividual (state) level, as the ultimate goal in understanding national interests.
Keywords: Western Balkans, NATO, security, common denominator, risks, cooperation, coordination, integration